The Distribution of wealth and the MPC: implications of new European data - Christopher D. Carroll; Jiri Slacalek; Kiichi Tokuoka (European Central Bank (ECB), 2014)
Using new micro data on household wealth from fifteen European countries, the Household Finance and Consumption Survey, we first document the substantial cross-country variation in how various measures of wealth are distributed across individual households. Through the lens of a standard, realistically calibrated model of buffer-stock saving with transitory and permanent income shocks we then study how cross-country differences in the wealth distribution and household income dynamics affect the marginal propensity to consume out of transitory shocks (MPC). We find that the aggregate consumption response ranges between 0.1 and 0.4 and is stronger (i) in economies with large wealth inequality, where a larger proportion of households has little wealth, (ii) under larger transitory income shocks and (iii) when we consider households only using liquid assets (rather than net wealth) to smooth consumption.
Keywords: D12; D31; D91; E21; 330; consumption dynamics; cross-country comparisons; liquid assets; MPC; wealth inequality